Kehidupan Keberagamaan Masyarakat Suku Akit di Desa Sonde Kabupaten Kepulauan Meranti - Hasbullah Hasbullah (Sosial Budaya, 2018)
This research was carried out on the basis that none of the people in this world, both simple and advanced who do not have a religion, even though they understand the religion in the simplest sense. The Akit Tribe is one of the Remote Indigenous Communities (KAT) that still survive in Riau Province. These people have interacted and interacted with other communities and their lives were no longer isolated. Thus, their culture has come into contact with the culture of other communities, including in religious life. Based on this phenomenon, this study was conducted to see their religious life after interacting and touching other cultures. This research is a descriptive study using qualitative methods. Data collection techniques used are in-depth interviews and observations. The informants of this research are the chiefs, traditional leaders, community leaders, religious leaders, and formal leaders. The results of this study indicate that the process of contact with other cultures slowly leads to changes in the culture of the Akit tribe, including in matters of religion. Nevertheless, formally they have embraced certain formal religions, but in practice they still retain their old beliefs and traditions. Thus, in religious life, the Akit Tribe people practice syncretism.